A Strategy for Alleviating Micro Arcing during HiPIMS Deposition of DLC Coatings - Vitelaru, Catalin; Parau, Anca Constantina; Constantin, Lidia Ruxandra; Kiss, Adrian Emil; Vladescu, Alina; Sobetkii, Arcadie; Kubart, Tomas (Materials, 2020)
In this work, we investigate the use of high power impulse magnetron sputtering (HiPIMS) for the deposition of micrometer thick diamond like carbon (DLC) coatings on Si and steel substrates. The adhesion on both types of substrates is ensured with a simple Ti interlayer, while the energy of impinging ions is adjusted by using RF (Radio Frequency) biasing on the substrate at −100 V DC self-bias. Addition of acetylene to the working Ar+Ne atmosphere is investigated as an alternative to Ar sputtering, to improve process stability and coatings quality. Peak current is maintained constant, providing reliable comparison between different deposition conditions used in this study. The main advantages of adding acetylene to the Ar+Ne gas mixture are an increase of deposition rate by a factor of 2, when comparing to the Ar+Ne process. Moreover, a decrease of the number of surface defects, from ~40% surface defects coverage to ~1% is obtained, due to reduced arcing. The mechanical and tribological properties of the deposited DLC films remain comparable for all investigated gas compositions. Nanoindentation hardness of all coatings is in the range of 25 to 30 GPa, friction coefficient is between 0.05 and 0.1 and wear rate is in the range of 0.47 to 0.77 × 10−6 mm3 N−1m−1.